The Role of the Project Owner in Agile Project Management: A Case Study of the Kinerjapro Application Development at PT.Menara Indonesia - Wibowo, Nurafni Revita; Syaifudin; Solihah, Binti (Intelmatics, 2025)
This study aims to design a web-based project management information system for monitoring internships at PT Menara Indonesia. The background of the study is the Merdeka Belajar Kampus Merdeka (MBKM) program, which enhances students' competencies in the workforce, as well as the challenges of manual internship monitoring, such as the risk of losing project records, limited storage, and inefficiency in communication and project coordination. The system is developed using the Agile Scrum method, following 5 sprints that include Product Backlog, Sprint Planning, Daily Scrum, Sprint Review, and Sprint Retrospective. The features developed include login, project and task management, messaging system, team member management, and basic report and event features. The Scrum implementation improves operational efficiency and data transparency. The result is a web-based project management information system that overcomes manual monitoring issues, increases efficiency, and facilitates better coordination among teams at PT Menara Indonesia, providing faster and more transparent information access.